Inverted “upside-down” esophageal fully-covered self-expanding metal stent is effective for temporary treatment of colorectal strictures: a pilot case series - Testoni, Pier Alberto; Fanti, Lorella; Antonucci, Enrico; Dabizzi, Emanuele (Endoscopy International Open, 2019)
Background and study aims Placement of a fully-covered self-expanding metal stent (FC-SEMS) is a valid alternative for benign and malignant colorectal strictures treatment. Despite the reportedly high technical success rate, stenting is still challenging, due to high rates of adverse events. Migration still represents the main issue, although several anti-migration systems have been proposed.Patients and methods Before insertion, esophageal Beta Niti-S FC-SEMSs were inverted and reloaded on the deployment device to invert the proximal and distal parts of the stent, with the largest end placed above the stricture to contrast peristaltic activity. The inverted “upside-down” Beta Niti-S FC-SEMS was placed in five consecutive patients: four pts with benign anastomotic stricture unresponsive to repeated balloon dilation and persisting for at least 10 weeks, and one with malignant rectal neoplasia. In five patients, six inverted FC-SEMSs were placed. Results The modified FC-SEMS did not migrate in 5/6 cases (83 %). Stent migration occurred in the neoplastic case, induced by neoadjuvant chemotherapy. The “upside-down” esophageal Beta Niti-S FC-SEMS stayed in place for an average of 6 weeks, achieving resolution of stricture in all patients but one, who required an additional stent placement, due to incomplete stricture resolution after 6 weeks. Conclusion The inverted esophageal Beta Niti-S FC-SEMSs proved to be effective in treating colorectal stricture in all cases, with no spontaneous migration or significant side effects, and achieved resolution of strictures where a traditional approach, recommended by guidelines, failed.